Pengaruh Pendidikan Karakter terhadap Prestasi Akademik Setingkat Menengah Pertama - Febrian, Rafico Rifki; Darmawan, Didit (TSAQOFAH, 2025)
This study aims to explore the influence of character education on the academic achievement of junior high school students. Through literature analysis and empirical data from previous research, it was found that character education has a significant impact on improving academic performance. The effective implementation of character education is carried out through collaboration between parents and teachers, creating an environment that supports students' character development. A strong character, shaped by internal motivation and external support, influences students' attitudes and behavior in the learning process. The study results indicate that with well-managed character education, junior high school students become more engaged, enthusiastic, and productive in achieving their educational goals. Engaging teaching methods, emotional support, and recognition of students' efforts play a crucial role in creating a positive learning atmosphere. Thus, this study highlights the importance of character education in supporting academic achievement and the overall development of junior high school students, helping shape individuals who are not only academically intelligent but also possess strong moral values.